Girls to the front: How redshirting and test-score gaps are affected by a change in the school-entry cut date. (June 2020) - Cook, Philip J.; Kang, Songman
Highlights: Uses novel source of variation – a legislated change in the cut date for school entry – to investigate age effects on standardized test scores and other academic outcomes. A change in entry cut date in NC narrowed the black-white test-score gaps for males born in the swing period (September and early October) and raised test scores for females relative to males for whites born in the swing period. It also narrowed the gaps between poor and non-poor students. Gaps in retention rates for grades 1–4 were also affected by the change in cut date. Changes in redshirting and greenshirting patterns induced by the reform suggest that parents (and school officials) are guided by the absolute age (maturity) of the child rather than age relative to classmates. Thus the state's choice of cut date had policy-relevant consequences that were unexpected and large enough to deserve consideration. Abstract: Most states have moved their public-school-entry cut date forward in recent years. In North Carolina the latest date by which a matriculant must turn 5 was recently changed from October 16th to August 31st. Those born in between the old and new cut dates (the "swing group"), formerly among the youngest entrants, became the oldest. Utilizing a comprehensive statewide administrative data set, we demonstrate that for the swing group the black-white standardized test-score gaps (3rd and 4th grade) has narrowed, and the gender gaps changed markedly to favor girls. These shifts are explained in part by the near elimination of redshirting for the swing group, and in part by gender differences in the gain to being older.